2002
DOI: 10.1034/j.1600-0749.2002.1o049.x
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Pathogenesis of Vitiligo: Imbalance of Epidermal Cytokines at Sites of Lesions

Abstract: Vitiligo is a skin disease that is caused by selective destruction of melanocytes and is characterized by white spots. Melanocytes and keratinocytes seem to exhibit a functional close relationship, mediated at least in part by keratinocyte-derived cytokines, which seem important for survival and activity of melanocytic cells. We wanted to investigate the hypothesis that in vitiligo the expression of epidermal cytokines may be modified compared with normal skin. In 15 patients with active, non-segmental vitilig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
288
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(305 citation statements)
references
References 25 publications
12
288
2
3
Order By: Relevance
“…Interestingly, in vitiligo, a decreased level of SCF has been found in the depigmented zone, in which melanocytes were thought to die by apoptosis. 47,48 Further, SCF production by keratinocytes is increased by ultraviolet B (UVB) radiation, which is known to increase nevi size and number. 49,50 In the same line, transgenic mice expressing elevated levels of SCF develop melanocyte dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in vitiligo, a decreased level of SCF has been found in the depigmented zone, in which melanocytes were thought to die by apoptosis. 47,48 Further, SCF production by keratinocytes is increased by ultraviolet B (UVB) radiation, which is known to increase nevi size and number. 49,50 In the same line, transgenic mice expressing elevated levels of SCF develop melanocyte dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies indicate that decreased TGFin vitiligo patients, and this could have a deleterious effect upon Treg cell function in these individuals [58][59][60]. In addition, serum concentrations of TGF-have been shown to be decreased in cases of active but not stable vitiligo, indicating that lower levels of the cytokine are positively correlated with disease progression [61].…”
Section: Transforming Growth Factor-mentioning
confidence: 99%
“…Several studies showed the role of peripheral blood and lesional cytokine expression in vitiligo patients. These suggested a role for epidermal cytokine imbalance in the pathogenesis of vitiligo [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Co-occurrence with autoimmune diseases seems to be dependent of the clinical type of vitiligo especially with nonsegmental type [2]; however, the observation is not as frequent when considering exclusively the segmental clinical type of vitiligo [4]. The changing in cytokines levels were reported in vitiligo affected skin compared with healthy skin suggesting that the cytokine production in epidermal microenvironment may play a role in pathogenesis of vitiligo [5,6]. Several studies showed the role of peripheral blood and lesional cytokine expression in vitiligo patients.…”
Section: Introductionmentioning
confidence: 99%